IMPLEMENTASI MODEL PEMBELAJARAN MATEMATIKA UNTUK MENSTIMULASI BERPIKIR KRITIS DI MGMP MATEMATIKA PURWOREJO - Setiana, Dafid Slamet; Ayuningtyas, Annis Deshinta; Supriyadi, Didi; Nisa, Ana Fitrotun; Fajarudin, Muhamad; Pardimin, Pardimin; Kusumaningrum, Betty; Susetyo, Agustinus Eko (UNIVERSITAS PGRI MADIUN, 2022)
Abstract.The education sector has also felt the impact of the Covid-19 pandemic, which can be said to be quite significant. The online learning policy launched by the government has been accepted and implemented by schools without careful planning. Teachers as the frontline in facilitating learning really feel the decline in the competence and quality of students' human resources, especially in mathematics subjects caused by students' relatively low critical thinking skills. This condition was complained by members of the Mathematics MGMP of Purworejo Regency. The complaint was then answered by the service team through community service activities by implementing a mathematics learning model to stimulate critical thinking. The purpose of implementing this massive learning model is to increase the innovation and competence of teachers of the Mathematics MGMP members of SMA Purworejo in implementing learning that can stimulate students' critical thinking skills. Community service activities will be carried out on December 21-24 2021 with the target of the Purworejo Mathematics MGMP. The stages of activities include socialization, dissemination, implementation, and evaluation. Through this activity, MGMP members gain a lot of knowledge related to learning models and students' critical thinking skills, gain inspiration and innovation in implementing mathematics learning, and through implementation in students, teachers can ultimately improve students' mathematical critical thinking skills. Abstrak. Sektor pendidikan turut merasakan dampak pandemi Covid-19 yang dapat dikatakan cukup signifikan. Kebijakan pembelajaran daring yang dicanangkan oleh pemerintah diterima dan diimplementasikan oleh sekolah tanpa perencanaan yang matang. Guru sebagai garda terdepan dalam memfasilitasi pembelajaran sangat merasakan turunnya kompetensi dan kualitas SDM siswa terutama pada mata pelajaran matematika yang diakibatkan oleh kemampuan berpikir kritis siswa yang relatif rendah. Kondisi ini dikeluhkan oleh anggota MGMP Matematika Kabupaten Purworejo. Keluhan tersebut kemudian dijawab oleh tim pengabdi melalui kegiatan pengabdian masyarakat dengan implementasi model pembelajaran matematika untuk menstimulasi berpikir kritis. Tujuan kegiatan implementasi model pembelajaran secara massive ini diharapkan dapat meningkatkan inovasi dan kompetensi guru anggota MGMP Matematika SMA Purworejo dalam melaksanakan pembelajaran yang dapat menstimulasi kemampuan berpikir kritis siswa. Kegiatan pengabdian masyarakat dilaksanakan pada tanggal 21-24 Desember 2021 dengan sasaran MGMP Matematika Purworejo. Adapun tahapan kegiatan meliputi sosialisasi, diseminasi, implementasi, dan evaluasi. Melalui kegiatan ini, anggota MGMP memperoleh banyak ilmu terkait model pembelajaran maupun kemampuan berpikir kritis siswa, memperoleh inspirasi dan inovasi dalam melaksanakan pembelajaran matematika, serta melalui implementasi pada siswa pada akhirnya guru dapat meningkatkan kemampuan berpikir kritis matematis siswa.